Microstructure evolution in Ni and Ni-superalloy based metallic-intermetallic laminate (MIL) composites. (August 2017) - Wang, Yu; Wang, Haoren; Liu, Xin; Vecchio, Kenneth S.
Abstract: Pure nickel and Nickel Alloy-X based Metallic-Intermetallic Laminate (MIL) composites were fabricated and investigated for their microstructure evolution, growth kinetics and microhardness distribution across the intermetallic/metal interfaces. Multi-phase layer structure with parabolic growth kinetics is shown in the nickel-based MIL composites. A two-phase eutectic layer along with a uniform layer form in the Alloy-X based MIL composites, which shows a mixed growth kinetic mechanism. The microhardness distribution across the intermetallic/metal interface of the two MIL composites was investigate with respect to the effects of texture and microstructure of the intermetallic phases. A simple intermetallic growth model is developed and validated for predicting the phase formation in binary or ternary reactions for synthesis of these MIL composites. Graphical abstract: A simple prediction rules based on solubility of the components in the reaction system has been established and validated for predicting the phase formation in the eutectic layer of ternary or quaternary reactions for Ni-based and Fe-based MIL composites. The growth of the reaction layers in Alloy-X/Al reaction can be described as a mixed kinetic growth mechanism existing in the eutectic layer and the uniform layer. In the present temperature range, the growth of uniform layer follows parabolic growth, which is mainly governed by lattice diffusion, while the growth of the eutectic layer follows linear growth controlled by the interface reaction.